Vanadium-titanium slag-based low-carbon cementing material and preparation method thereof

Through the coordinated excitation of solid waste materials such as vanadium titanium slag and steel slag and the use of composite active excitants, vanadium titanium slag-based low-carbon gelling materials that do not require high-temperature calcination are prepared, which solves the problem of low utilization rate of industrial waste and realizes the high performance and resource utilization of low-carbon gelling materials.

CN119841562APending Publication Date: 2025-04-18CHANGZHOU GREEN MART CONSTR TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510053904.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The utilization rate of industrial waste such as vanadium titanium slag and steel slag is low, resulting in waste of resources and environmental pressure, and the prior art is difficult to effectively stimulate its gelling performance.

Method used

A variety of solid waste materials such as vanadium titanium slag, steel slag, citric acid slag are used to synergize and stimulate the products, and through composite active exciters and grinding technology, vanadium titanium slag-based low-carbon gelling materials that do not require high-temperature calcination are prepared.

Benefits of technology

The production of low-carbon gelling materials has been achieved, with excellent bending resistance, durability and corrosion resistance, meet low-carbon requirements, reduce energy consumption and carbon emissions, and promote the resource utilization of solid waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841562A_ABST
    Figure CN119841562A_ABST
Patent Text Reader

Abstract

The invention relates to a vanadium-titanium slag-based low-carbon cementing material and a preparation method thereof. The vanadium-titanium slag-based low-carbon cementing material comprises the following raw materials: 50-65% of vanadium-titanium slag, 15-24% of steel slag, 14-18% of citric acid slag, 5-8% of lithium slag and 1.0-2.0% of a composite active exciting agent, except the composite active exciting agent, the rest of the raw materials in the ratio are dry base materials which are dried until the water content is less than 1%; the preparation method comprises the following steps: 1, mixing and pretreating the citric acid slag and the steel slag; 2, drying the raw materials; 3, carrying out ultrafine grinding on the raw material part; step 4, performing coarse grinding on the raw material part; and 5, uniformly mixing the ultrafine powder obtained in the step 3 and the coarse powder obtained in the step 4 according to a ratio to obtain the vanadium-titanium slag-based low-carbon cementing material. Various solid waste materials are utilized for synergistic excitation, production can be achieved without high-temperature calcination, and the low-carbon significance is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of low-carbon cementitious materials, in particular to a vanadium-titanium slag-based low-carbon cementitious material and a preparation method thereof. Background Art

[0002] Vanadium-titanium slag refers to a kind of granular or blocky industrial waste slag obtained by quenching with water or naturally cooling the high-temperature slag discharged during the smelting process of pig iron using vanadium-titanium magnetite as raw material. For every ton of iron smelted, 0.3 to 0.6 tons of waste slag can be discharged. The chemical composition of vanadium-titanium slag is similar to that of ordinary blast furnace slag, mainly CaO, SiO2, Al2O3, MgO, etc. The difference is that its TiO2 content is high, usually between 16% and 25%. This leads to the mineral composition of vanadium-titanium slag being dominated by crystalline minerals such as titanium pyroxene, perovskite without hydraulic activity, bayite, spinel, etc., and the amount of glassy components formed is significantly reduced, and the activity is greatly reduced. Therefore, the current utilization rate of vanadium-titanium slag is very low. A large amount of vanadium-titanium slag cannot be reasonably utilized, which not only causes waste of resources and occupies land area, but also puts great pressure on the environment and ecological balance.

[0003] Steel slag is a by-product of the steelmaking process. It is composed of various oxides formed by the oxidation of impurities such as silicon, manganese, phosphorus, and sulfur in pig iron during the smelting process, as well as salts generated by the reaction of these oxides with solvents. Its main chemical composition is similar to that of cement clinker, and its main components are CaO, SiO2, Al2O3, MgO, Fe2O3, MnO, etc. Its physical phase composition is mainly dicalcium silicate, RO phase, dicalcium ferrite, and free calcium oxide. It has potential gelling properties, but its low activity and long-term stability problems caused by free calcium oxide and free magnesium oxide hinder its large-scale application in the building materials industry. my country's steel industry is well developed, and the output of steel slag accounts for 10% to 15% of crude steel output, with an annual output of more than 100 million tons. At present, the comprehensive utilization rate of steel slag in my country is less than 30%, and effective risk control and resource utilization and disposal are needed.

[0004] Citric acid residue is the industrial waste residue from the production of citric acid. Sulfuric acid is added during the production process to obtain waste residue mainly containing hydrated calcium sulfate. It is in the form of mud and contains a small amount of calcium citrate and sulfuric acid. The main component of citric acid residue is similar to gypsum, and its chemical formula is CaSO4·2H2O.

[0005] Solid waste-based cementitious materials refer to raw materials rich in silicon and aluminum substances (typically granulated blast furnace slag) as the core, which are stimulated by alkaline substances (such as steel slag) and gypsum. Based on the double salt effect and the tetracoordinate isomorphism effect of silicon, the formation and dissolution of calcium sulfoxide double salt is the driving force, which promotes the dissociation and repolymerization of silicon (aluminum) oxygen tetrahedrons in the slag, and finally forms a hardened structure with needle-rod-shaped calcium sulfoxide crystals wrapped in a large amount of amorphous CS-(A)-H gel, which has good strength and stability.

[0006] By utilizing the principle of solid waste-based cementitious materials, cementitious materials are prepared with vanadium-titanium slag, steel slag, citric acid slag, etc. as raw materials, which reduces the pressure of solid waste accumulation on the environment and realizes resource utilization. At the same time, the production process does not require high-temperature calcination, greatly reducing energy consumption and carbon emissions. The products produced have high bending resistance, durability and corrosion resistance, excellent performance and low-carbon significance, good market prospects and broad application fields, and are of great significance to both environmental protection and economic development. Summary of the invention

[0007] The technical problem to be solved by the present invention is: in order to overcome the deficiencies in the prior art, a vanadium-titanium slag-based low-carbon cementitious material and a preparation method thereof are provided, which utilizes the synergistic stimulation of multiple solid waste materials and can be produced without high-temperature calcination, thus having low-carbon significance.

[0008] The technical solution adopted by the present invention is: a vanadium-titanium slag-based low-carbon cementitious material, comprising the following raw materials in weight percentage: 50-65% of vanadium-titanium slag, 15-24% of steel slag, 14-18% of citric acid slag, 5-8% of lithium slag, and 1.0-2.0% of a composite active activator; the raw materials in the above ratio, except for the composite active activator, are calculated as dry basis materials dried to a moisture content of less than 1%.

[0009] Furthermore, the vanadium-titanium slag includes the following raw materials in weight percentage: CaO is 28-38%, SiO2 is 20-30%, Al2O3 is 10-20%, MgO is 5-15%, and TiO2 is less than 20%.

[0010] Furthermore, the steel slag includes the following raw materials in weight percentage: CaO is 40-55%, SiO2 is 10-25%, Al2O3 is 0-10%, MgO is 0-10%, Fe2O3 is 10-25%, and P2O5 is 0-5%.

[0011] Furthermore, the CaSO4·2H2O content in the citric acid residue is greater than 80%, and the water content is 5-20%.

[0012] Furthermore, the lithium slag includes SiO2 and Al2O3, and the total content of the two is greater than 60%.

[0013] Furthermore, the composite active stimulant is prepared according to the ratio of nano silica sol: sodium metasilicate: triisopropanolamine: water = 5:2:0.5:2.5.

[0014] Furthermore, the pH value of the nano-silica sol is 9.5-10, and the average particle size of SiO2 in the nano-silica sol is 7-10 nm.

[0015] At the same time, the present invention also provides a method for preparing a vanadium-titanium slag-based low-carbon cementitious material, comprising the following steps:

[0016] The first step is to pre-treat the mixture of citric acid slag and steel slag: the moisture content of citric acid slag and steel slag is detected respectively, the wet basis is weighed according to the dry basis weight of the two 1: (1.1-1.3), 4.5-5.5% of quicklime is added to the total dry basis weight, and then soaked in water, left to age for 20-28 hours, and finally washed and filtered;

[0017] The second step is drying the raw materials: drying the mixed slag of vanadium-titanium slag, lithium slag, citric acid slag and steel slag until the moisture content is less than 1%;

[0018] The third step is to grind the raw materials into ultrafine powder: weigh various raw materials according to the proportion, mix them evenly, put them into the stainless steel ball mill of the omnidirectional planetary ball mill, and run the ball mill for 60 to 120 minutes until the powder particle size parameters are: D10 particle size is 0.7 to 1.2 μm, D25 particle size is 1.5 to 3.0 μm, D50 particle size is 3.5 to 4.5 μm, D90 particle size is 16.0 to 20 μm, and D97 particle size is 25.0 to 30.0 μm;

[0019] The fourth step is to grind the raw materials into coarse powder: weigh various raw materials according to the proportion, mix them evenly, put them into the stainless steel ball mill of the omnidirectional planetary ball mill, and run the ball mill for 10 to 15 minutes until the powder particles have the following particle size parameters: D10 particle size is 1.8 to 2.5 μm, D25 particle size is 4.8 to 6.0 μm, D50 particle size is 13.0 to 15.0 μm, D90 particle size is 43.0 to 48.0 μm, and D97 particle size is 65.0 to 75.0 μm;

[0020] The fifth step is to uniformly mix the ultrafine powder obtained in the third step with the coarse powder obtained in the fourth step in a ratio of (2.0-3.0): (7.0-8.0) to obtain a vanadium-titanium slag-based low-carbon cementitious material.

[0021] Furthermore, the capacity of the stainless steel ball mill in the third step and the fourth step is 4-6L, the ball-to-material ratio is (7-9):1, the stainless steel balls are arranged in a ratio of large ball: medium ball: small ball = 4:3:3, and the rotation speed is set to 250-350r / min.

[0022] Specifically, the diameter of the large ball is 11-13 mm, the diameter of the medium ball is 7-9 mm, and the diameter of the small ball is 3-5 mm.

[0023] The beneficial effects of the present invention are:

[0024] 1. The production process is simple, the cost of raw materials is extremely low, no calcination is required, and carbon emissions are significantly reduced compared to traditional cement production;

[0025] Second, a large amount of solid waste is utilized, and industrial waste such as vanadium-titanium slag, steel slag, lithium slag, and citric acid slag is utilized as resources, which reduces the occupation of land and creates additional economic value, which has the significance of green recycling and sustainable development of solid waste utilization;

[0026] 3. Through scientific design and ratio, active stimulants are preferably selected, and under the dual physical and chemical excitation modes, the vanadium-titanium slag-based low-carbon cementitious material of the present invention has excellent performance. Referring to the strength test method in the national standard GB / T175-2023 "General Portland Cement", the vanadium-titanium slag-based cementitious material of the present invention has a strength test result of 3-day flexural strength ≥7.0 MPa, 3-day compressive strength ≥26.0 MPa, 28-day flexural strength ≥9.0 MPa, 28-day compressive strength ≥47.0 MPa, 56-day flexural strength ≥11.0 MPa, 56-day compressive strength ≥56.0 MPa, which meets the requirements of 42.5 grade cement, and the later strength growth is higher than that of ordinary Portland cement; in addition, the vanadium-titanium slag-based low-carbon cementitious material of the present invention also has the unique advantages of low hydration heat, low shrinkage, and strong resistance to sulfate erosion, and can be better applied to large volume, large area or marine engineering application scenarios to avoid cracking and sulfate erosion. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a graph showing the particle size test results of the embodiment and the comparative example. DETAILED DESCRIPTION

[0028] The embodiments of the present invention are described in detail below. The embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments.

[0029] Example 1

[0030] The vanadium-titanium slag-based low-carbon cementitious material of this embodiment includes the following raw materials in weight percentage: 57% vanadium-titanium slag, 19% steel slag, 17% citric acid slag, 5% lithium slag, and 2% composite active activator; except for the composite active activator, the rest of the raw materials in the above ratio are calculated as dry basis materials dried to a moisture content of less than 1%.

[0031] Vanadium-titanium slag includes the following raw materials in weight percentage: CaO is 35%, SiO2 is 28%, Al2O3 is 18%, MgO is 14%, and TiO2 is 5%. Vanadium-titanium slag is a water-quenched slag formed by smelting pig iron with vanadium-titanium magnetite as raw material, and the high-temperature slag discharged during the smelting process is water-quenched and cooled. Under the rapid cooling condition, the glass content in the slag particles is higher than that in natural cooling, and the reaction activity is better. In order to avoid the slag activity being too low due to too high TiO2 content, vanadium-titanium slag with a TiO2 content of less than 20% is selected.

[0032] The steel slag includes the following raw materials in weight percentage: CaO is 46%, SiO2 is 15%, Al2O3 is 8%, MgO is 7%, Fe2O3 is 20%, and P2O5 is 4%. As the main alkalinity providing substance, the steel slag has a significant impact on the reaction of the solid waste-based cementitious material. According to a large number of experiments on the cementitious material of the present invention, the steel slag alkalinity D=(CaO+MgO) / (SiO2+P2O5)≥2.5 is required.

[0033] The CaSO4·2H2O content in the citric acid residue is 82% and the water content is 7%.

[0034] The lithium slag includes SiO2 and Al2O3, and the total content of the two is 64%. The lithium slag used in the present invention is the industrial residue produced by producing lithium carbonate by sulfuric acid method after calcining spodumene at a high temperature of 1000-1200°C. The main chemical components are SiO2 and Al2O3, and the total content of the two should be greater than 60%, showing a high volcanic ash activity.

[0035] The composite active activator is prepared according to the ratio of nano silica sol: sodium metasilicate: triisopropanolamine: water = 5:2:0.5:2.5. Specifically, the composite active activator used in the present invention is a liquid activator, which is a mixed solution of nano silica sol, sodium metasilicate, and triisopropanolamine, and is prepared according to the ratio of nano silica sol: sodium metasilicate: triisopropanolamine: water = 5:2:0.5:2.5.

[0036] The pH of nano silica sol is 9.6, the average particle size of SiO2 in nano silica sol is 8nm, and the mass fraction of SiO2 is 30%. Sodium metasilicate is pentahydrate sodium metasilicate powder, which is tetrahydrate of disodium dihydrogen orthosilicate with two cations, and its solubility is 50g / 100g water at 20℃. Triisopropanolamine is an alcoholamine compound with amino group and alcoholic hydroxyl group, and is a surfactant. Its spatial stereoscopic structure of alkane chain and hydroxyl group isomerization makes it have excellent particle dispersibility and grinding aid effect.

[0037] The method for preparing the vanadium-titanium slag-based low-carbon cementitious material of this embodiment comprises the following steps:

[0038] The first step is pretreatment of citric acid slag and steel slag mixture: the moisture content of citric acid slag and steel slag is detected respectively, the wet basis is weighed according to the dry basis weight of the two of 1:1.1, 5% of the total weight of quicklime is added, and then soaked in water, left to age for 24 hours, and finally washed and filtered; this step is to remove the acid and some impurities in the citric acid slag, and at the same time, it can also eliminate some free calcium oxide and magnesium oxide in the steel slag.

[0039] The second step is drying the raw materials: drying the mixed slag of vanadium-titanium slag, lithium slag, citric acid slag and steel slag to a moisture content of less than 1% to prevent the ball mill from causing harmful phenomena such as sticking of the grinding and sticking of the balls;

[0040] The third step is to grind the raw materials into ultrafine powder: weigh various raw materials according to the proportion, including 57% vanadium-titanium slag, 36% mixed slag of steel slag and citric acid slag, 5% lithium slag and 2.0% composite active activator, mix the various raw materials evenly, and put them into the stainless steel ball mill of the omnidirectional planetary ball mill. The capacity of the stainless steel ball mill is 5L, the ball-to-material ratio is 8:1, and the stainless steel balls are configured in the ratio of large ball (diameter 12mm): medium ball (diameter 8mm): small ball (diameter 4mm) = 4:3:3. The speed is set to 300r / min, the ball mill running time is 100min, and the powder particles are ground to the following particle size parameters: D10 particle size is 0.7-1.2μm, D25 particle size is 1.5-3.0μm, D50 particle size is 3.5-4.5μm, D90 particle size is 16.0-20μm, and D97 particle size is 25.0-30.0μm;

[0041] The fourth step is to grind the raw materials into coarse powder: weigh various raw materials according to the proportion, including 57% vanadium-titanium slag, 36% mixed slag of steel slag and citric acid slag, 5% lithium slag and 2.0% composite active activator, mix the various raw materials evenly, put them into the stainless steel ball mill of the omnidirectional planetary ball mill, and grind them into powder particles with the following particle size parameters: D10 particle size is 1.8-2.5 μm, D25 particle size is 4.8-6.0 μm, D50 particle size is 13.0-15.0 μm, D90 particle size is 43.0-48.0 μm, and D97 particle size is 65.0-75.0 μm;

[0042] The fifth step is to mix the ultrafine powder obtained in the third step and the coarse powder obtained in the fourth step in a ratio of 3.0:7.0 to obtain a vanadium-titanium slag-based low-carbon cementitious material.

[0043] Example 2

[0044] The vanadium-titanium slag-based low-carbon cementitious material of this embodiment includes the following raw materials in weight percentage: 58.5% vanadium-titanium slag, 18% steel slag, 16% citric acid slag, 6% lithium slag, and 1.5% composite active activator; except for the composite active activator, the rest of the raw materials in the above ratio are calculated as dry basis materials dried to a moisture content of less than 1%.

[0045] The vanadium-titanium slag includes the following raw materials in weight percentage: 37% CaO, 26% SiO2, 19% Al2O3, 10% MgO and 8% TiO2.

[0046] The steel slag includes the following raw materials in weight percentage: 50% CaO, 18% SiO2, 7% Al2O3, 8% MgO, 14% Fe2O3, and 3% P2O5.

[0047] The CaSO4·2H2O content in the citric acid residue is 84% ​​and the water content is 10%.

[0048] The lithium slag includes SiO2 and Al2O3, and the total content of the two is 67%.

[0049] The composite active activator is prepared according to the ratio of nano silica sol: sodium metasilicate: triisopropanolamine: water = 5:2:0.5:2.5.

[0050] The pH of nano-silica sol is 9.8, and the average particle size of SiO2 in nano-silica sol is 9nm.

[0051] The method for preparing the vanadium-titanium slag-based low-carbon cementitious material of this embodiment comprises the following steps:

[0052] The first step is pretreatment of mixing citric acid slag and steel slag: the moisture content of citric acid slag and steel slag is detected respectively, the wet basis is weighed according to the dry basis weight of 1:1.2, quicklime of 5% of the total dry basis weight is added, and then soaked in water, left to age for 24 hours, and finally washed and filtered;

[0053] The second step is drying the raw materials: drying the mixed slag of vanadium-titanium slag, lithium slag, citric acid slag and steel slag until the moisture content is less than 1%;

[0054] The third step is to grind the raw materials into ultrafine powder: weigh various raw materials according to the proportion, including 58.5% vanadium-titanium slag, 34% mixed slag of steel slag and citric acid slag, 6% lithium slag and 1.5% composite active activator, mix the various raw materials evenly, and put them into the stainless steel ball mill of the omnidirectional planetary ball mill. The capacity of the stainless steel ball mill is 5L, the ball-to-material ratio is 8:1, and the stainless steel balls are configured in the ratio of large ball (diameter 12mm): medium ball (diameter 8mm): small ball (diameter 4mm) = 4:3:3. The speed is set to 300r / min, the ball mill running time is 80min, and the powder particles are ground to the following particle size parameters: D10 particle size is 0.7-1.2μm, D25 particle size is 1.5-3.0μm, D50 particle size is 3.5-4.5μm, D90 particle size is 16.0-20μm, and D97 particle size is 25.0-30.0μm;

[0055] The fourth step is to grind the raw materials into coarse powder: weigh various raw materials according to the proportion, including 57% vanadium-titanium slag, 36% mixed slag of steel slag and citric acid slag, 5% lithium slag and 2.0% composite active activator, mix the various raw materials evenly, put them into the stainless steel ball mill of the omnidirectional planetary ball mill, and grind them into powder particles with the following particle size parameters: D10 particle size is 1.8-2.5 μm, D25 particle size is 4.8-6.0 μm, D50 particle size is 13.0-15.0 μm, D90 particle size is 43.0-48.0 μm, and D97 particle size is 65.0-75.0 μm;

[0056] The fifth step is to mix the ultrafine powder obtained in the third step and the coarse powder obtained in the fourth step in a ratio of 3.0:7.0 to obtain a vanadium-titanium slag-based low-carbon cementitious material.

[0057] Example 3

[0058] The vanadium-titanium slag-based low-carbon cementitious material of this embodiment includes the following raw materials in weight percentage: 58% vanadium-titanium slag, 17% steel slag, 16% citric acid slag, 8% lithium slag, and 1% composite active activator; except for the composite active activator, the rest of the raw materials in the above ratio are calculated as dry basis materials dried to a moisture content of less than 1%.

[0059] The vanadium-titanium slag includes the following raw materials in weight percentage: 33% CaO, 27% SiO2, 17% Al2O3, 13% MgO and 10% TiO2.

[0060] The steel slag includes the following raw materials in weight percentage: CaO is 53%, SiO2 is 20%, Al2O3 is 5%, MgO is 6%, Fe2O3 is 11%, and P2O5 is 5%.

[0061] The CaSO4·2H2O content in the citric acid residue is 85% and the water content is 12%.

[0062] The lithium slag includes SiO2 and Al2O3, and the total content of the two is 68%.

[0063] The composite active activator is prepared according to the ratio of nano silica sol: sodium metasilicate: triisopropanolamine: water = 5:2:0.5:2.5.

[0064] The pH of nano-silica sol is 9.7, and the average particle size of SiO2 in nano-silica sol is 10nm.

[0065] The method for preparing the vanadium-titanium slag-based low-carbon cementitious material of this embodiment comprises the following steps:

[0066] The first step is pretreatment of mixing citric acid slag and steel slag: the moisture content of citric acid slag and steel slag is detected respectively, the wet basis is weighed according to the dry basis weight of 1:1.3, 5% of the total weight of quicklime is added, and then soaked in water, left to age for 24 hours, and finally washed and filtered;

[0067] The second step is drying the raw materials: drying the mixed slag of vanadium-titanium slag, lithium slag, citric acid slag and steel slag until the moisture content is less than 1%;

[0068] The third step is to grind the raw materials into ultrafine powder: weigh various raw materials according to the proportion, including 58% vanadium-titanium slag, 33% mixed slag of steel slag and citric acid slag, 8% lithium slag and 1% composite active activator, mix the various raw materials evenly, and put them into the stainless steel ball mill of the omnidirectional planetary ball mill. The capacity of the stainless steel ball mill is 5L, the ball-to-material ratio is 8:1, and the stainless steel balls are configured in the ratio of large ball (diameter 12mm): medium ball (diameter 8mm): small ball (diameter 4mm) = 4:3:3. The speed is set to 300r / min, the ball mill running time is 60min, and the powder particles are ground to the following particle size parameters: D10 particle size is 0.7-1.2μm, D25 particle size is 1.5-3.0μm, D50 particle size is 3.5-4.5μm, D90 particle size is 16.0-20μm, and D97 particle size is 25.0-30.0μm;

[0069] The fourth step is to grind the raw materials into coarse powder: weigh various raw materials according to the proportion, including 57% vanadium-titanium slag, 36% mixed slag of steel slag and citric acid slag, 5% lithium slag and 2.0% composite active activator, mix the various raw materials evenly, put them into the stainless steel ball mill of the omnidirectional planetary ball mill, and grind them into powder particles with the following particle size parameters: D10 particle size is 1.8-2.5 μm, D25 particle size is 4.8-6.0 μm, D50 particle size is 13.0-15.0 μm, D90 particle size is 43.0-48.0 μm, and D97 particle size is 65.0-75.0 μm;

[0070] The fifth step is to uniformly mix the ultrafine powder obtained in the third step and the coarse powder obtained in the fourth step in a ratio of 2.0:8.0 to obtain a vanadium-titanium slag-based low-carbon cementitious material.

[0071] Comparative Example 1

[0072] The difference from Example 1 is that no composite active activator is added, and this part of the mass is added to the vanadium-titanium slag, that is, the vanadium-titanium slag is 59%, the steel slag is 19%, the citric acid slag is 17%, and the lithium slag is 5%.

[0073] Comparative Example 2

[0074] The difference from Example 1 is that no lithium slag is added, and this part of the mass is added to the vanadium-titanium slag, that is, the vanadium-titanium slag is 62%, the steel slag is 19%, the citric acid slag is 17%, and the composite active activator is 2%.

[0075] Comparative Example 3

[0076] The difference from Example 1 is that the addition amount of the mixed slag of steel slag and citric acid slag is adjusted from 36% to 25%, and the reduced mass is added to the vanadium-titanium slag.

[0077] Comparative Example 4

[0078] The difference from Example 1 is that the addition amount of the mixed slag of steel slag and citric acid slag is adjusted from 36% to 45%, and the increased mass is deducted from the vanadium-titanium slag.

[0079] Comparative Example 5

[0080] The difference from Example 1 is that the gelled material is obtained by ball milling for only 15 minutes.

[0081] Comparative Example 6

[0082] The difference from Example 1 is that the gelled material is obtained by ball milling for only 120 minutes.

[0083] The above-mentioned Examples 1 to 3 and Comparative Examples 1 to 6 were subjected to detailed performance tests, and the compressive strength, flexural strength, standard consistency water consumption, setting time, and stability tests were conducted with reference to the national standard GB / T175-2023 "General Portland Cement". In addition, the shrinkage test was conducted using the NELD-CS730 non-contact bellows shrinkage and expansion tester. The shrinkage rate was tested 28 days after final setting according to the ratio of standard sand to cementitious material of 1:1 and a water-cement ratio of 0.4. The hydration heat was tested for 7 days at a water-cement ratio of 0.5 using an I-Cal 8000HPC isothermal calorimeter. The 90-day sulfate erosion resistance of the test blocks made according to the standard mortar ratio was tested with reference to GB / T50082-2009 "Standard Test Method for Long-term Performance and Durability of Ordinary Concrete". The specific particle size was tested using a dry laser particle size analyzer. The specific test results are shown in Tables 1 and 2. Figure 1 shown.

[0084] Table 1 Example test results

[0085]

[0086]

[0087] Table 2 Comparative Example Test Results

[0088]

[0089] It can be seen from Table 1 and Table 2 that Examples 1, 2, and 3 fully meet the performance requirements of 42.5 grade general-purpose Portland cement within the preferred ratio range of the present invention. The cementitious material of the present invention can replace cement and be applied in a large number of scenarios, and its hydration heat and hardening autogenous shrinkage are significantly lower than those of Portland cement, and it has excellent resistance to sulfate erosion, and has better application effect in large-volume concrete and marine engineering concrete.

[0090] The strength of comparative example 1 before and after is much smaller than that of example 1, and the average particle size is significantly larger than that of example 1, indicating that the composite active activator of the present invention can effectively activate the activity of vanadium-titanium slag and has a good grinding effect. - 、HSiO3 - Plasma can promote the dissolution of silicon phase in slag, generate more CSH gel, reduce the amount of ettringite generated, and prevent a large amount of ettringite from covering unhydrated particles and hindering the later hydration reaction. The reaction of silicon phase and aluminum phase in the system is in a good equilibrium state, the degree of hydration reaction is maximized, the final product is more, and the hardened structure strength is higher. Triisopropanolamine is an effective grinding aid, which can make the particles finer within the same ball milling time.

[0091] The strength of Comparative Example 2 is lower than that of Example 1, indicating that a small amount of lithium slag can promote the hydration reaction of the cementitious material of the present invention, which not only improves the early strength, but also optimizes the hardened slurry structure and improves the later strength.

[0092] The strength of Comparative Example 3 is much lower than that of Example 1 because the amount of steel slag and citric acid slag is significantly reduced, indicating that citric acid slag, as a sulfate activator, provides SO4 2- The hydration reaction of the cementitious material of the present invention is greatly affected. When the amount of citric acid residue is too small, SO4 in the system 2- The concentration growth rate slows down, affecting the dissolution of slag in the early stage and SO4 in the later stage. 2- The lack of slag leads to a decrease in the degree of hydration reaction, and the strength of the material is significantly reduced in the early and late stages. The reduction of slag leads to insufficient alkalinity in the solution, the activity of the slag is difficult to be effectively stimulated, the hydration reaction proceeds slowly, the hydration products are reduced, and finally the strength is significantly reduced.

[0093] The strength of Comparative Example 4 is much lower than that of Example 1, because the amount of steel slag and citric acid slag is too much, indicating that SO4 2- If the concentration increases too fast, the rapid formation of large amounts of ettringite in the early stage will hinder the further hydration of the slag. Too much slag will lead to excessive alkalinity in the solution, which will also affect the morphology of the ettringite after formation and be detrimental to the strength.

[0094] Comparative Example 5 has the lowest early strength and the longest setting time, indicating that the particle size has a significant impact on the hydration reaction. On the one hand, the reduction in specific surface area leads to a reduction in the area where the hydration reaction occurs, and the generated hydration products are sharply reduced. On the other hand, the mechanical force activation effect of the ball mill is reduced, and the activity of the slag particles is significantly reduced.

[0095] The strength of Comparative Example 6 is higher than that of Example 1, mainly in the early stage, and the higher degree in the later stage is not large, but the water requirement of the standard consistency increases sharply, indicating that the ultrafine particles react rapidly in the early stage, the early strength is high, and the reaction rate decreases after being wrapped by the hydration product in the later stage, and the final strength improvement is limited. Too fine particles will greatly increase the adsorption of water, have a great impact on fluidity in engineering applications, and significantly increase the production cost, which is not cost-effective.

[0096] The technical principle of the present invention is:

[0097] First, CaO, MgO and C2S in ultrafine slag particles react with water to provide a large amount of OH - , rapidly increasing the alkalinity of the solution, the Si-O-Si bonds in the silicon-oxygen tetrahedron of the ultrafine vanadium-titanium slag particles break in an alkaline environment to form -Si-OH and -Si-O-. In addition to the destruction of the silicon-oxygen tetrahedron, the Ca-O and Mg-O in the slag will also break, dissolving Ca 2+ Mg 2+The plasma enters the liquid phase, and as the hydration reaction proceeds, the aluminum-oxygen tetrahedron in the slag is also destroyed to form -Al-OH. At this time, the Al2O3 in the ore powder will also react to form H3AlO4 2- and AlO2 - When there is a large amount of H2SiO4 in the system 2- 、HSiO4 3- and H3AlO4 2- In an alkaline environment, these ions and the Ca dissolved from the mineral powder itself 2+ and Ca in citric acid residue 2+ Combined to form a large amount of amorphous CSH and CAH gel. At the same time, the SO4 2- , Ca 2+ and AlO2 - Hydration occurs to form needle-shaped ettringite crystals (3CaO·Al2O3·3CaSO4·32H2O). Under alkaline conditions, ettringite is a complex salt with extremely low solubility, and its solubility product constant is 10 -111.6 After the reaction is generated, it quickly precipitates in the form of crystals, reducing the SO4 in the solution 2- , Ca 2+ and AlO2 - The concentration of vanadium titanium slag breaks the dissolution balance between the aluminosilicate minerals in the vanadium titanium slag and the soluble aluminum in the solution, accelerates the dissolution of aluminum in the aluminosilicate minerals, and accelerates the dissociation of aluminum-oxygen tetrahedrons from the polymer of silicon (aluminum) oxygen tetrahedrons, and then repolymerizes to form hydrated calcium silicate (aluminum) acid gel. The needle-shaped ettringite crystals in the hydration product overlap each other and fill in the hydrated calcium silicate (aluminum) acid gel. At the same time, other unhydrated particles will also fill in the pores of the hydration product, eventually forming a hydrated hardened body of the cementitious material.

[0098] The addition of lithium slag can shorten the setting time and improve the strength. This is because the content of Al2O3 in lithium slag is more than 20%, and it also contains a large amount of amorphous SiO2, and its active ingredient content is higher than that of slag. Lithium slag is a porous structure with a large internal surface area and strong adsorption capacity. It can quickly adsorb various ions and dissolve faster in an alkaline environment to generate SiO4 4- 、Al(OH) 4- 、AlO 2- Plasma first generates hydrated calcium silicate and ettringite crystals, which in turn promote the hydrolysis of slag and can become an activating material for the hydration reaction.

[0099] Citric acid residue can not only provide the Ca required for the reaction 2+ and SO4 2- , which also contains some calcium citrate, the molecular formula is C 12 H 10Ca3O 14 It contains two highly polar hydroxyl groups and six carboxyl groups. The hydroxyl groups are easily adsorbed on the surface of the powder particles to form an adsorption film, which reduces the surface energy of the particles and thus enhances the grinding effect. In the later stage of the hydration reaction, the carboxyl groups have a strong chelating effect and can react with the Ca in the slag glass. 2+ It forms water-soluble complexes, destroys the vitreous structure, promotes the dissolution of unreacted slag particles, generates more ettringite and CSH gel, optimizes the pore structure, and greatly enhances the material strength.

[0100] The addition of nano-silica sol in the composite active activator can promote the hydration of the silicon phase (increase and densification of C-(A)-SH gel) and inhibit the hydration of the aluminum phase (reduction of the amount of calcium sulfonate generated and the consumption of gypsum). If the aluminum phase is hydrated too quickly or too early, the calcium sulfonate crystals will adhere to the surface of the unhydrated particles, affecting the subsequent hydration reaction. The addition of nano-silica sol will make the hydration kinetics of the aluminum phase and the silicon phase in the cementitious material more coordinated, thereby promoting the hydration of the slag, and generating more hydrated calcium silicate (aluminum) gel, filling the large pores and refining the small pores, making the hardened slurry structure more uniform and dense, and improving its overall performance. Sodium metasilicate pentahydrate dissolves in water and ionizes OH - 、Na + 、HSiO3 - Plasma, on the one hand, NaOH can promote the breakage of silicon-oxygen bonds on the surface of mineral powder glass and repolymerization, on the other hand, silicate ions can combine with Ca 2+ CSH gel is generated, so that more CSH gel is generated in the system, making the hardened structure denser. Triisopropanolamine is a surfactant that can be adsorbed on the surface of particles during grinding to form a film, producing a steric hindrance effect and a dispersing and lubricating effect, reducing the agglomeration of particles during grinding and improving grinding efficiency.

[0101] The present invention utilizes a grinding method to mix some raw materials and then conduct ultrafine grinding to make the raw material particles ultrafine. It is a physical excitation method that effectively improves the hydration activity. Ultrafine grinding is not only a process of reducing the particle size, but also its crystal structure and surface will undergo significant changes. Along with the grinding process, the lattice bond energy of the slag decreases, the grain size decreases, the crystal deformation increases, the structure is distorted, the specific surface area is larger, and more reaction surfaces are exposed. Its microscopic filling effect and activity are higher. Ultrafine slag particles are adsorbed on the surface of coarse particles, which can accelerate the dissociation and repolymerization of silicon oxygen and aluminum oxygen tetrahedron in the slag in an alkaline environment, promote the formation of early hydration products, and use the chemical driving force generated by the imbalance of ion concentration in the solution to promote the dissolution and hydration of coarse slag particles. It is more economical than ultrafine all particles, and is more in line with the particle stacking model, which is conducive to improving the density and fluidity of the system.

[0102] The invention discloses a vanadium-titanium slag-based low-carbon cementitious material and a preparation method thereof, based on the theoretical guidance of the double salt effect and the tetracoordinate isomorphism effect of silicon, with vanadium-titanium ore powder as the main excited material, and citric acid slag and steel slag respectively providing the SO4 required for the hydration reaction. 2- and OH - , realize sulfate activation and low-alkali activation of vanadium-titanium ore powder, add lithium slag rich in active silicon and aluminum to promote the hydration process of the system, add composite active activator to further promote the depolymerization of slag particles, generate more hydration products, and improve the early and late strength of the material. In addition to the above chemical activation, the present invention also uses particle grading design to ultra-finely grind part of the raw materials, and then coarsely grind with the remaining raw materials. The ultra-fine particles are more strongly activated by mechanical force, resulting in more lattice distortion and local damage, forming more defects, and greatly enhancing the reaction activity. The ultra-fine particles are adsorbed on the surface of the coarse particles to cause hydration reactions faster to consume various ions and destroy the Ca in the solution. 2+ 、SO4 2- 、SiO4 4- 、AlO2 2- The balance of plasma concentration provides a chemical driving force to promote the dissolution of the coarse particle surface. As the reaction continues, hydration products are slowly generated, overlapping each other and eventually forming a hardened body with good strength.

[0103] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A vanadium-titanium slag-based low-carbon cementitious material, characterized in that: The invention comprises the following raw materials in weight percentage: 50-65% of vanadium-titanium slag, 15-24% of steel slag, 14-18% of citric acid slag, 5-8% of lithium slag and 1.0-2.0% of composite active activator; except for the composite active activator, the rest of the raw materials in the above proportion are calculated as dry basis materials dried to a moisture content of less than 1%.

2. The vanadium-titanium slag-based low-carbon cementitious material according to claim 1, characterized in that: The vanadium-titanium slag comprises the following raw materials in weight percentage: 28-38% of CaO, 20-30% of SiO2, 10-20% of Al2O3, 5-15% of MgO, and less than 20% of TiO2.

3. The vanadium-titanium slag-based low-carbon cementitious material according to claim 1, characterized in that: The steel slag comprises the following raw materials in weight percentage: 40-55% CaO, 10-25% SiO2, 0-10% Al2O3, 0-10% MgO, 10-25% Fe2O3 and 0-5% P2O5.

4. The vanadium-titanium slag-based low-carbon cementitious material according to claim 1, characterized in that: The CaSO4·2H2O content in the citric acid residue is greater than 80%, and the water content is 5-20%.

5. The vanadium-titanium slag-based low-carbon cementitious material according to claim 1, characterized in that: The lithium slag includes SiO2 and Al2O3, and the total content of the two is greater than 60%.

6. The vanadium-titanium slag-based low-carbon cementitious material according to claim 1, characterized in that: The composite active activator is prepared according to the ratio of nano silica sol: sodium metasilicate: triisopropanolamine: water = 5:2:0.5:2.

5.

7. The vanadium-titanium slag-based low-carbon cementitious material according to claim 6 is characterized by: The pH value of the nano-silica sol is 9.5-10, and the average particle size of SiO2 in the nano-silica sol is 7-10 nm.

8. A method for preparing the vanadium-titanium slag-based low-carbon cementitious material as claimed in claim 1, characterized in that: The following steps are involved: The first step is to pre-treat the mixture of citric acid slag and steel slag: the moisture content of citric acid slag and steel slag is detected respectively, the wet basis is weighed according to the dry basis weight of the two 1: (1.1-1.3), 4.5-5.5% of quicklime is added to the total dry basis weight, and then soaked in water, left to age for 20-28 hours, and finally washed and filtered; The second step is drying the raw materials: drying the mixed slag of vanadium-titanium slag, lithium slag, citric acid slag and steel slag until the moisture content is less than 1%; The third step is to grind the raw materials into ultrafine powder: weigh various raw materials according to the proportion, mix them evenly, put them into the stainless steel ball mill of the omnidirectional planetary ball mill, and run the ball mill for 60 to 120 minutes until the powder particle size parameters are: D10 particle size is 0.7 to 1.2 μm, D25 particle size is 1.5 to 3.0 μm, D50 particle size is 3.5 to 4.5 μm, D90 particle size is 16.0 to 20 μm, and D97 particle size is 25.0 to 30.0 μm; The fourth step is to grind the raw materials into coarse powder: weigh various raw materials according to the proportion, mix them evenly, put them into the stainless steel ball mill of the omnidirectional planetary ball mill, and run the ball mill for 10 to 15 minutes until the powder particles have the following particle size parameters: D10 particle size is 1.8 to 2.5 μm, D25 particle size is 4.8 to 6.0 μm, D50 particle size is 13.0 to 15.0 μm, D90 particle size is 43.0 to 48.0 μm, and D97 particle size is 65.0 to 75.0 μm; The fifth step is to uniformly mix the ultrafine powder obtained in the third step with the coarse powder obtained in the fourth step in a ratio of (2.0-3.0): (7.0-8.0) to obtain a vanadium-titanium slag-based low-carbon cementitious material.

9. The method for preparing the vanadium-titanium slag-based low-carbon gelled material according to claim 8, characterized in that: The capacity of the stainless steel ball mill in the third step and the fourth step is 4-6L, the ball-to-material ratio is (7-9):1, the stainless steel balls are arranged in a ratio of large ball: medium ball: small ball = 4:3:3, and the rotation speed is set to 250-350r / min.

10. The method for preparing the vanadium-titanium slag-based low-carbon gelled material according to claim 9, characterized in that: The diameter of the large ball is 11-13 mm, the diameter of the medium ball is 7-9 mm, and the diameter of the small ball is 3-5 mm.

Citation Information

Cited By

  • Steel slag-based multi-solid-waste synergistic low-carbon cementing material and preparation method thereof

    CN121225895A